STRATEGI PENGEMBANGAN POTENSI AGROWISATA DI KECAMATAN TANANTOVEA KABUPATEN DONGGALA - Saleh, Khaeruddin; Jokolelono, Eko; Anam, Haerul (Katalogis, 2021)
The objectives of the research are to know the agro tourism characteristics and to develop strategy of agro tourism potential in Tanantovea District, Donggala Regency. The data are analyzed through SWOT Analysis.The results of the research show that the internal problem faced by the people is promoting agro tourism extensively, less on commodity cultivation aspect, things of supporting production are not available yet and the people are not support on agro tourism. As same as external, the treats are faced by the people namely: land use change, broken environment caused by nature disaster or human error, and there is the development in another place. Based on SWOT analysis, it can be concluded that the development potential strategy of Agro Tourism on Nupabomba village can beÂ  developed through using agriculture horticulture, namely vegetables, fruits, coffee, people local culture of Nupabomba people as the oldest village (Ventira culture), and nature tourism. While the development potential strategy on Guntarano is using waterfall to build retention basin as the freshwater tourism object and union commodity development.